The Effect Of Project Based Learning (Pjbl) Model On Students’ Writing Procedure Text Assisted By Youtube - Dinda Tsurmaiza Sitorus; Putri Lidiana Permata Sari (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2026)
This study aimed to find out The Effect of Project Based Learning (PjBL) Model on Students’ Writing Procedure Text Assisted by Youtube at Grade XI of SMA Negeri 1 Simpang Empat. This research used a quantitative approach with a quasi-experimental design by applying a pre-test and post-test design. The population of this study consisted of grade XI students in the 2025/2026 academic year. The sample was divided into two groups, namely the experimental group (XI IPA 1) and the control group (XI IPA 2), with 35 students in each class. The experimental group was taught by using the Project-Based Learning model assisted by YouTube, while the control group was taught by using conventional teaching methods. The instrument used in collecting the data was a writing test in the form of a procedure text, which was administered as a pre-test and post-test. The result showed that the mean score of the experimental group increased from 58,42 in the pre-test to 80,29 in the post-test, while the control group increased from 53,57 in the pre-test to 66,57 in the post-test. The result of the t-test calculation showed that the value of t-test was 4,51, which was higher than the value of t-table 1,995 at the level of significance 0,05 with the degree of freedom (df) 68. Therefore, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It can be concluded that Project-Based Learning assisted by YouTube has a significant effect on students’ ability in writing procedure text at the grade XI of SMA Negeri 1 Simpang Empat. Keywords: Project-Based Learning, YouTube, Writing Ability, Procedure Text.